The pains and reliefs of the transitions into and out of spousal caregiving. A cross-national comparison of the health consequences of caregiving by gender. (November 2019) - Uccheddu, Damiano; Gauthier, Anne H.; Steverink, Nardi; Emery, Tom
Abstract: Spousal caregiving offers a unique opportunity to investigate how gender shapes the influence of care responsibilities on health at older ages. However, empirical evidence supporting a causal link between the transitions into and out of caregiving and health is mixed. This study investigates the influence of spousal care transitions on the health of older men and women living in 17 European countries. We use five waves of the Survey of Health, Ageing and Retirement in Europe (SHARE) between the years 2004 and 2015 for a total of 43, 435 individuals and 117, 831 observations. Health is defined as a Frailty Index calculated from 40 items. Caregiving is defined as intensive help with personal care provided to spouses. Results from asymmetric fixed-effects linear regression models show that the transitions into caregiving have a detrimental effect on health. On the contrary, the transitions out of caregiving have in most cases no beneficial consequences on health. Most importantly, we found evidence supporting differential effects of caregiving transitions by gender and welfare arrangement: the transitions out of caregiving are associated with better health conditions only for Southern and Eastern European women. Our study highlights the asymmetric and gendered nature of care transitions and suggests that the impact of caregiving is somewhat permanent and has long lasting effects for the caregiver. Policies should account for this asymmetry when assessing the impact and consequences of caregiving. Highlights: Transitions into spousal caregiving are generally associated with reduced health. Transitions out of caregiving have usually no beneficial consequences on health. The effects of caregiving transitions vary by gender and welfare arrangement. Policies need to consider the gendered and asymmetric consequences of caregiving.